Bacterial Cellulose Powder as A Filler in a Matrix Composite from Oil Palm Trunk - Panggabean, Hasbullah; Ahmad, Selamat Triono; Sukardi, Sukardi; Yahfizham, Yahfizham; Thahir, Muhammad Taufiq (Green Engineering Society, 2024)
The paper is to reveal the bacterial cellulose powder as a filler for a composite matrix with an oil palm trunk. The use of oil palm trunks is excellent because of their abundant availability and because they can reduce waste. It is low-density, environmentally friendly, inexpensive, non-toxic, and easily degraded as a matrix that produces hydrogels obtained from cross-linking. This research is a laboratory experiment that makes films by masks using the bacterial cellulose powder obtained through enzyme hydrolysis fillers with the addition of 1%, 2%, 3%, 4%, and 5%. Bio-composite films are readily biodegradable, so the films made from extracting oil palm trunks with stem starch are environmentally friendly. The pH value of the five preparations for film gel masks was the shelf life of bio-composite, which could last for 21 days. Characterization of film masks includes physical properties and analysis of chemical composition, where the amount of water in the film will decrease as the size of the polymer that makes up the film matrix increases. The treatment that produced bio-composite films with the best mechanical properties under the addition of bacterial cellulose powder was 3% filler. The cellulose bacterium can be applied as a filler for making composites by modifying the oil palm trunk as a matrix composite.